Removal of dsRNA byproducts using affinity chromatography - Nathaniel E. Clark; Mateusz Kozarski; Sinem Demirel Asci; Jurgen Van den Heuvel; Matt R. Schraut; Roger A. Winters; Kelley Kearns; Thomas C. Scanlon; Senne Dillen (Molecular Therapy: Nucleic Acids)
Double-stranded RNA (dsRNA) molecules are immunogenic byproducts of in vitro transcription of single-stranded RNA (ssRNA). Removal of dsRNA from ssRNA is difficult because the byproducts have similar sizes, sequences, and charges to the desired ssRNA. Here, we describe a dsRNA-specific affinity resin that selectively removes dsRNA from ssRNA. Affinity purification reduced dsRNA levels by >100-fold, to as low as ∼0.00007% w/w of total mRNA, with no negative impact on RNA integrity. The purified RNA, synthesized with standard nucleotides, induced no inflammatory response in a reporter cell line assay designed to measure innate immune responses. Purified RNA induced greater protein expression and healthier cells. The immunogenicity of the affinity-purified RNA with standard nucleotides compares favorably to RNA synthesized with modified nucleotides and purified with cellulose or reverse-phase high-performance liquid chromatography (HPLC). dsRNA affinity purification provides a facile and scalable solution to the problem of immunogenic dsRNA byproducts in transcribed RNA. This approach will improve quality and safety of RNA vaccines and therapeutics.